A case of kwashiorkor in a child with congenital hypothyroidism - Tangkilisan, Helena Aneke; Wijayanto, Teguh; Wiriadinata, Sugianto (Paediatrica Indonesiana, 2001)
A 12-year-old Indonesian girl with the body weight of 9.8 kg and length 78 cm was admitted to the Department of Child Health, Manado General Hospital with kwashiorkor and congenital hypothyroidism. The main complaint was edema starting 3 weeks before admission. Physical examination showed body weight for age (BW/A) 14.3%, body weight for body length (BW/BL) 66.0% and body length for age (BL/A) 49.1%. On admission she looked severely ill, apathetic, with hypothermia and hypotonia. Almost all signs and symptoms of kwashiorkor and congenital hypothyroidism were found accompanied bronchopneumonia and dermatologic problems. Laboratory findings showed severe anemia, leukocytosis, hypoproteinemia, hyponatremia, hypokalemia, elevated thyroid stimulating hormone and low level of Thyroxine-4. Bone age equaled to a newborn baby bone age. There was no thyroid tissue on thyroid ultrasound examination. The patient was treated for severe protein energy malnutrition and ThyraxR. Problems of kwashiorkor could been solved well but not with the congenital hypothyroidism. She was discharged from hospital after 2 months treatment and till now at 14th year of age with her developmental milestones equals to that of 8 month old baby.